2018
DOI: 10.1038/s41598-018-25853-3
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic endothelial nanotubes induced by wheat germ agglutinin and thrombin

Abstract: Endothelial barrier formation is maintained by intercellular communication through junctional proteins. The mechanisms involved in maintaining endothelial communication subsequent to barrier disruption remain unclear. It is known that low numbers of endothelial cells can be interconnected by homotypic actin-driven tunneling nanotubes (TNTs) which could be important for intercellular transfer of information in vascular physiology. Here we sought insight into the triggers for TNT formation. Wheat germ agglutinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Part of the biochemical cascade that results in VTE includes activation of thrombin, a serine protease that converts fibrinogen to fibrin. A recent elegant study demonstrated the ability of thrombin to induce TNTs in endothelial cells (Pedicini et al, 2018 ), providing further support to the notion that TNTs play a previously uncovered role in this cancer-related process.…”
Section: Heterotypic Interactions Between Malignant Cells and Stroma mentioning
confidence: 67%
“…Part of the biochemical cascade that results in VTE includes activation of thrombin, a serine protease that converts fibrinogen to fibrin. A recent elegant study demonstrated the ability of thrombin to induce TNTs in endothelial cells (Pedicini et al, 2018 ), providing further support to the notion that TNTs play a previously uncovered role in this cancer-related process.…”
Section: Heterotypic Interactions Between Malignant Cells and Stroma mentioning
confidence: 67%
“…While hypoxia promotes the formation of TNTs, TNTs in turn stimulate a potential positive feedback loop by mediating intercellular transfer of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) between connected cells, from cancer cells to ECs, to stimulate angiogenesis [ 147 ]. Thrombin induce TNTs in ECs [ 161 ]. Since cancer provides a prothrombotic state, this further supports a role for TNTs interplay between cancer cells and ECs.…”
Section: Endothelial Cells and Tunneling Nanotubesmentioning
confidence: 99%
“…TNTs can also occur between ECs ( Figure 3 ), but we still have little understanding of the role of homotypic endothelial-to-endothelial TNTs or how they are formed. It has been suggested that ECs maintain Ca 2+ signals during an injury on monolayer integrity by forming endothelial-to-endothelial TNTs [ 161 ] This induction depends on the highly sialylated CD31 protein, an adhesion molecule that is largely restricted to ECs. In cultured ECs (HUVEC) thrombin-that disrupt endothelial cell barrier and promote cell signaling and reorganization of the actin cytoskeleton readily causes the appearance of TNTs [ 161 ].…”
Section: Endothelial Cells and Tunneling Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…TnTs can also transmit information unidirectionally or bi-directionally [ 4 , 7 , 8 ]. Additionally, TnTs can be homotypic in that they connect similar cells (tumor cell to tumor cell) [ 7 , 9 ] or heterotypic meaning they connect different cell types (like macrophages to tumor cells) [ 10 ]. High-resolution microscopy and 3-dimensional reconstructions confirmed that TnTs are present in invasive malignancies, including human ovarian adenocarcinoma [ 5 ], providing evidence that TnTs are a characteristic of highly invasive cancers with metastatic potential, such as OC.…”
Section: Introductionmentioning
confidence: 99%